2008
DOI: 10.1634/stemcells.2007-0737
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory and Anti-Angiogenic Role of Mesenchymal Stem Cells in Corneal Wound Healing Following Chemical Injury

Abstract: To investigate the anti-inflammatory and anti-angiogenic effects of mesenchymal stem cells (MSC) in the chemically burned corneas, we mechanically removed the corneal epithelium of rats after 100% alcohol instillation. The rats were then randomized into four groups: fresh media, conditioned media derived from the MSC culture (MSC-CM), MSC applied topically to the damaged corneas for 2 hours immediately after the injury or MSC-CM applied either once or 3 times per day for 3 consecutive days. Corneal surface was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
264
0
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(300 citation statements)
references
References 38 publications
20
264
0
16
Order By: Relevance
“…We chose to administer the MSCs before transplantation (day À7) as previous studies have shown enhanced efficacy when applied pretransplantation in preclinical models of cardiac (34) and kidney (35) transplantation. To date, a number of groups have investigated the ability of MSCs to repair chemically damaged corneas (20,(36)(37)(38) but relatively few have reported on the effects of MSCs on corneal allograft survival (22,39). To our knowledge, we show here for the first time that MSCs derived from a thirdparty strain are effective in prolonging corneal allograft survival.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We chose to administer the MSCs before transplantation (day À7) as previous studies have shown enhanced efficacy when applied pretransplantation in preclinical models of cardiac (34) and kidney (35) transplantation. To date, a number of groups have investigated the ability of MSCs to repair chemically damaged corneas (20,(36)(37)(38) but relatively few have reported on the effects of MSCs on corneal allograft survival (22,39). To our knowledge, we show here for the first time that MSCs derived from a thirdparty strain are effective in prolonging corneal allograft survival.…”
Section: Discussionmentioning
confidence: 70%
“…Considering the regenerative potential and profound immunosuppressive effects of MSCs, MSC therapy is a promising approach for the treatment of inflammatory diseases and prevention of graft rejection (for review see [19]). Recently, treatment of experimental corneal injuries in rabbits and limbal stem cell deficiencies in rats with MSCs has been reported (20,21); however, very little is known about the role of MSCs in the prevention of corneal allograft rejection. One recent study did report the therapeutic benefit of human MSC infusion in a fully allogeneic mouse model of cornea transplantation (22).…”
Section: Introductionmentioning
confidence: 99%
“…Further, VEGF overexpressing bone marrow stem cells demonstrate greater protection of injured tissue than controls. Thus, VEGF, HGF, and FGF2 may be important paracrine signaling molecules in stem cell-mediated angiogenesis, protection, and survival (26)(27)(28)(29)(30) . …”
Section: B1) Increased Angiogenesismentioning
confidence: 99%
“…12 It improves the corneal reepithelialization and reduces the anti-inflammatory acute phase through the release of soluble factors. 13 It is constituted of a single layer of epithelial cells that lie on the basement membrane, which is adjacent to a compact layer of collagen. AM is easily isolated from the placenta after a cesarean delivery and can be cryopreserved for several months.…”
mentioning
confidence: 99%